Refuge 33.2 General Issue (accessible print version) (Refuge: Canada's Journal on Refugees, 2017)
This is an accessible copy of issue 33.2. It is certified by an IAAP WAS/ADS certified accessibility professional as meeting or exceeding all accessibility conformance requirements with respect to: AODA WCAG 2.0 Level A and AA PDF/UA.